2012
DOI: 10.1634/theoncologist.2011-0275
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab, Cyclophosphamide, Doxorubicin, Vincristine, and Prednisone with or Without Radiotherapy in Primary Mediastinal Large B-Cell Lymphoma: The Emerging Standard of Care

Abstract: After completing this course, the reader will be able to:1. Describe the effect of the addition of rituximab to standard CHOP chemotherapy on the outcome of patients with primary mediastinal large B-cell lymphoma.2. Explain potential changes in the use of radiotherapy and aggressive chemotherapy in the rituximab era.This article is available for continuing medical education credit at CME.TheOncologist.com. CME CME

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
96
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(102 citation statements)
references
References 43 publications
4
96
0
2
Order By: Relevance
“…The 5-year OS, PFS and local control rates for early-stage patients were 73.6, 69.9 and 92.6% for chemotherapy and RT, and 50.8% (P=0.076), 36.9% (P=0.008) and 56.4% (P<0.001) for chemotherapy alone, respectively (5). However, another study conducted by a group from Greece suggested that the addition of RT to RCHOP chemotherapy did not improve the 5-year PFS (92 vs. 93%; P>0.2) and 5-year OS (96 vs. 100%; P>0.2) rates compared with RCHOP alone (15). The National Cancer Institute group has presented encouraging data with regard to 51 PMLBCL patients who were treated with dose-adjusted etoposide, doxorubicin, cyclophosphamide, vincristine, prednisone and rituximab (DA-EPOCH-R) chemotherapy, without the routine use of RT.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The 5-year OS, PFS and local control rates for early-stage patients were 73.6, 69.9 and 92.6% for chemotherapy and RT, and 50.8% (P=0.076), 36.9% (P=0.008) and 56.4% (P<0.001) for chemotherapy alone, respectively (5). However, another study conducted by a group from Greece suggested that the addition of RT to RCHOP chemotherapy did not improve the 5-year PFS (92 vs. 93%; P>0.2) and 5-year OS (96 vs. 100%; P>0.2) rates compared with RCHOP alone (15). The National Cancer Institute group has presented encouraging data with regard to 51 PMLBCL patients who were treated with dose-adjusted etoposide, doxorubicin, cyclophosphamide, vincristine, prednisone and rituximab (DA-EPOCH-R) chemotherapy, without the routine use of RT.…”
Section: Discussionmentioning
confidence: 93%
“…The current National Comprehensive Cancer Network 2013 guidelines recommended rituximab as the first-line treatment for PMLBCL. Rituximab combined with chemotherapy has been confirmed to be very effective and safe for PMLBCL in multiple studies (14,15,22), and the superiority of certain intensive regimens over CHOP for treatment of PMBCL disappeared once rituximab was added (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who received rituximab had a superior 3-year event-free survival (78% vs. 52% in the chemotherapy arm alone)-because of small numbers, an OS difference was not appreciated. Most patients in this analysis received preplanned mediastinal radiation which improved remission rates (93,94). It is important to consider that the MInT study was confined to patients with a low IPI score ( 1) and therefore did not include the entire spectrum of patients with this disease.…”
Section: Treating Pmblmentioning
confidence: 99%
“…PMBCL has represented only a small minority of patients included in randomized trials to date, so the preponderance of data in this disease is retrospective in nature. Though outcome of DLBCL does appear improved in the rituximab era [12,13], modern R-CHOP still appears to be insufficient therapy for many patients with PMBCL, with a rate of primary refractory disease that approaches 20% [14], and with the majority of patients achieving remission still relying on radiation consolidation. A recent phase II trial of dose-adjusted EPOCH-R suggests improved outcomes and reduced need for radiation in PMBCL, further suggesting that R-CHOP may not represent the optimal chemotherapy platform in this particular variant of DLBCL [15].…”
mentioning
confidence: 99%